2014
DOI: 10.2224/sbp.2014.42.2.331
|View full text |Cite
|
Sign up to set email alerts
|

How Retaking the Entrance Examination Can Enhance Student Quality of Life at University

Abstract: We examined how the experience of retaking the college entrance examination (RCEE), along with levels of resilience and social support, affect individuals' experience of life change at university, their satisfaction with university life, and how meaningful they perceived their lives to be. We analyzed survey data from 524 university students in Korea (204 men and 320 women; 203 students with RCEE experience and 321 students with no RCEE experience). Results showed that students with RCEE experience underwent a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Finding meaning in life is a critical dilemma for these students undergoing great mental and behavioral development. Students who were retaking the college entrance examination experienced a positive life change and found greater meaning in university life [ 77 ]. However, those with less impulse control and meaning in life may be more susceptible to problematic behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Finding meaning in life is a critical dilemma for these students undergoing great mental and behavioral development. Students who were retaking the college entrance examination experienced a positive life change and found greater meaning in university life [ 77 ]. However, those with less impulse control and meaning in life may be more susceptible to problematic behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals with high self-esteem have strong emotion control ability and adaptability. They are enthusiastic and generous in their life, and often greet new things with a positive attitude (Baumeister et al, 2003), which have a positive influence towards their cognition, motivation, emotions and social behavior, making individuals more willing to pursue the meaning of real life (Lee & Jung, 2014). Previous studies have shown that there is a significant positive correlation between self-esteem and core self-evaluations (Wang, Liu, & Jackson, 2016), to be specific, the higher the self-esteem level, the more positive the self-esteem and self-confidence they have, and the more reasonable self-identification and positive self-evaluation they own.…”
Section: Introductionmentioning
confidence: 99%